Operating Capacity, Sales Growth, Managerial Agency Costs, Ownership Structure on Financial Distress in Indonesian Companies - Puspasari, Oktaviani Rita; Zahra, Salsabila; Purnama*, Dendi; Embuningtyas, Sandra Sukma (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This research aims to examine the influence of operational capacity, sales growth, managerial agency costs, managerial ownership, and institutional ownership on financial distress. The research method used is both descriptive and verificative. The study's population comprises companies in the transportation and logistics sector listed on the Indonesia Stock Exchange from 2017 to 2021. A total of 23 companies over five years, resulting in 115 data observations, were selected using purposive sampling. Hypothesis testing was conducted using panel data regression analysis. The research findings indicate that operational capacity and sales growth have a significant negative impact on financial distress. However, managerial agency costs and managerial ownership have a significant positive impact on financial distress. Meanwhile, institutional ownership also has a significant negative impact on financial distress. This study contributes to the corporate governance literature by predicting factors related to financial distress and providing empirical evidence for the use of the Springate Method in predicting financial distress. Keywords: Operating Capacity; Sales Growth; Managerial Agency Costs; Ownership Structure; Financial Distress Abstrak Penelitian ini bertujuan untuk menguji pengaruh kapasitas operasi, pertumbuhan penjualan, biaya keagenan manajerial, kepemilikan manajerial, dan kepemilikan institusional terhadap financial distress. Metode yang digunakan adalah deskriptif dan verifikatif. Populasi penelitian yaitu perusahaan sektor jasa transportasi dan logistik yang terdaftar di Bursa Efek Indonesia tahun 2017-2021. Jumlah sampel sebanyak 23 perusahaan selama 5 tahun atau 115 data observasi menggunakan teknik purposive sampling. Pengujian hipotesis menggunakan analisis regresi data panel. Temuan penelitian menunjukkan bahwa kapasitas operasi dan pertumbuhan penjualan berpengaruh negatif signifikan terhadap kesulitan keuangan. Namun biaya keagenan manajerial dan kepemilikan manajerial berpengaruh positif signifikan terhadap financial distress. Sementara itu, kepemilikan institusional juga berpengaruh negatif signifikan terhadap financial distress. Penelitian ini memberikan literatur mengenai peran mekanisme tata kelola perusahaan dalam memprediksi kesulitan keuangan dan memberikan bukti empiris penggunaan Metode Springate dalam memprediksi kesulitan keuangan. Kata Kunci: Kapasitas Operasional; Pertumbuhan Penjualan; Biaya Agensi Manajerial; Kepemilikan Manajerial; Kesulitan Keuangan